THE OEDIPUS COMPLEX IN EUGENE O’NEILL’S DESIRE UNDER THE ELMS - Sumarsono, Irwan; Fanani, Abu; Masofa, Ima (Lire Journal (Journal of Linguistics and Literature), 2022)
This research was conducted to analyze the Oedipus complex of Eben’s in Eugene O’Neil’s play entitled Desire Under the Elms. To analyze it, the writers use the psychological approach, especially Freud’s psychoanalysis theory. The writers got the main source of the data from the play, while the supporting data, the writers got from literary books, journals of English Literature, and the internet. Data were gathered then they were examined using the descriptive-analytic techniques. The focus of the study was divided into three discussions, namely the factors behind the reasons why Eben had the Oedipus complex, what made him have a rivalry with his own father, and had a forbidden relationship with his stepmother, Abbie. The forbidden relationship between Eben and Abbie is the manifestation of Eben’s Oedipus complex and his way to break his father’s deep heart as his revenge for his mother’s death. The study found out that Eben’s Oedipus complex was influenced more by Eben’s id than his ego and superego.